ICEmST contributes to colonization of Salmonella in the intestine of piglets - Nobuo Arai; Tomoyuki Shibahara; Reina Nishiura; Yukino Tamamura-Andoh; Hayate Nishiura; Yoshihiro Muneta; Hiroshi Sawada; Ayako Watanabe-Yanai; Taketoshi Iwata; Masato Akiba; Masahiro Kusumoto (Scientific Reports)
Abstract Salmonella enterica serovar 4,[5],12:i:- sequence type 34 (ST34) has recently become a global concern for public and animal health. The acquisition of mobile genetic element ICEmST, which contains two copper tolerance gene clusters, cus and pco, influences the epidemic success of this clone. Copper is used as a feed additive in swine at levels that potentially lead to selection pressure for Enterobacteriaceae; however, it remains unclear whether the copper tolerance system of ICEmST functions in vivo. We performed competition assays with Salmonella 4,[5],12:i:- ST34 wildtype (WT) and deletion mutants of ICEmST (ΔICEmST, Δcus, and Δpco) in groups of mice fed 0, 150, and 500 ppm CuSO4. In the competition of WT against ΔICEmST and Δcus, the competitive index of the 500 ppm-fed group was significantly lower than that of the 0 ppm-fed group. In the swine experiment, all individuals were fed 150 ppm CuSO4. The number of ICEmST-positive strain in the feces was significantly greater than that of ICEmST-negative strain. The serum inflammatory markers were significantly increased in swine infected with the ICEmST-positive strain. These data suggest that ICEmST, especially cus, provides Salmonella with the ability to colonize in the intestine, even at high copper concentrations, leading to swine salmonellosis.